THE INFLUENCE OF BRAND LOYALTY, PERCEIVED QUALITY AND BRAND TRUST ON REPEAT PURCHASE OF UNILEVER PRODUCTS - Audi Prima Ramadhani; Rizky Eka Febriansah; Mochamad Rizal Yulianto (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to examine the influence of brand loyalty, perceived quality, and brand trust on consumers repurchase decisions for Unilever products amid intensified competition and boycott issues in Indonesia. Method: A quantitative research approach was employed with data collected from 96 respondents through questionnaires, supported by secondary data from journals, books, and official websites. Data were analyzed using SPSS software, employing multiple linear regression along with validity, reliability, normality, multicollinearity, heteroscedasticity, t-tests, F-tests, and coefficient of determination (R²) analyses. Results: The findings reveal that brand loyalty, perceived quality, and brand trust each have a significant positive effect on repurchase behavior, indicating that consumers’ confidence and attachment to the brand remain key determinants of repeat purchases even during brand-related crises. Novelty: This study contributes to consumer behavior research by highlighting how trust and loyalty sustain repurchase intentions under boycott conditions, providing practical insights for brand resilience strategies in the Indonesian manufacturing industry.